Kondisi Kondisi Kesehatan Lingkungan Sekolah Dasar di Kecamatan Kota Padang Kabupaten Rejang Lebong - Persada, Pipin Dian (JURNAL BUANA, 2026)
The objectives of this study are: 1. to evaluate the cleanliness of human waste disposal facilities (latrines) and water storage systems within the school setting, and 2. to examine the presence of wastewater disposal facilities in schools within Padang City District. This study employs a quantitative descriptive approach. there are 7 public elementary schools located in Padang City District, Rejang Lebong Regency. Data was collected through observation, interviews, distributing questionnaires, and documentation, and analyzed using percentage techniques (%).Sampling was conducted using the proportional sampling technique. (1.) The health status of the school environment is evaluated based on the cleanliness of latrines/toilets and the utilization of clean water in 7 elementary schools, there are 5 schools in the clean category (71.42%), and there are 2 schools in the unclean category (28.57%) . The participation of all students is tasked with cleaning latrines/toilets at school, including cleaning before long holidays. (2.) Wastewater drainage systems in 7 schools, for schools that dispose of wastewater through septic tanks as much as (57.14%) and for schools which drain wastewater into sewers as much as (42.85%).